Analysis Of Fatherless Girls' Matchmaking Preferences on Tiktok Content - Bagus Aditya Nugroho; Muhammad Hafizh Hidayatullah (Journal of Psychology and Social Sciences, 2025)
Fatherless girls are vulnerable to social, psychological, and behavioral problems. This condition influences their partner selection, which is often linked to unmet emotional needs. This study aims to analyze the partner preferences of fatherless girls on the TikTok platform and explore the implications for their social and emotional well-being. Using a qualitative approach with content analysis, data were collected from 10 TikTok videos that met specific criteria, namely: accounts with more than 1,000 followers, over 500 comments, and content creators who were either experts on fatherless issues or individuals with lived experience. Data were analyzed through systematic observation of the videos and user comments to identify recurring themes and patterns. The results show that fatherless girls' partner preferences are heavily shaped by emotional needs for a father figure, such as the search for security and the desire to avoid similar negative experiences in the future. The conclusion of this study is that partner preferences are not only based on personal choice but also an emotional response to past affectional emptiness. These findings contribute to a psychological understanding of the relationship between family conditions and partner selection behavior, and they encourage further research on other digital platforms. The novelty of this research lies in its use of TikTok as an emerging digital space to study partner preference behavior, offering fresh insights into how father absence and unmet emotional needs manifest in online relational expressions.